PENGARUH PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT KRISTA PESONA ADIBUSANA JAKARTA - Rajagukguk, Pater; Kartawijaya, Feri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Every customer would want satisfaction in receiving a service. Customer satisfaction can be achieved if customers receive services in accordance with the required and expected. This study aims to analyze the effect of service on customer satisfaction at PT Krista Pesona Adibusana Jakarta conducted for five working days with the number of visitors 102. By using the formula Al-Rashid, set sample of 50 customers. Sampling technique using simple random sampling method. From the stastistic analysis with the help of spss version 22, conducted correlation test, regression test and test of determination. The results showed that there is a significant influence between service variables on customer satisfaction variables. So the service is a very important thing to note for customer satisfaction